Correlations between dentoskeletal variables and deep bite in Class II Division 1 individuals - Leandro Silva Marques; Mônica Costa Armond; Maria Letícia Ramos-Jorge; Raquel Gonçalves Vieira de Andrade; Ana Maria Bolognese (Sociedade Brasileira de Pesquisa Odontológica, 2011)
This study aimed to evaluate the cephalometric pattern of Class II Division 1 individuals with deep bite, and to determine possible correlations between dentoskeletal variables and deep bite. Comparisons were also made between genders and cases that were to be treated both with and without premolar extraction. A total of 70 lateral cephalograms were used, from both male (n = 35) and female (n = 35) individuals with an average age of 11.6 years, who simultaneously presented with ANB > 5º and overbite > 4 mm. Statistical analysis involved parametric (t-test) and non-parametric (Mann-Whitney) tests for independent samples, as well as the Spearman correlation test (p < 0.05). The values of Go-Me, Ar-Pog, PM-1 and PM-CMI were higher in males (p < 0.05). However, no significant differences were found among the averages of the cephalometric measurements when the sample was divided by treatment with and without extraction. Deep bite was positively correlated to the PM-1 and SNA measurements, and negatively correlated to the Go-Me, Ar-Pog, SNB and SNGoMe measurements. The main factors associated with the determination of deep bite in Angle's Class II Division 1 cases were: greater lower anterior dentoalveolar growth and/or lower incisor extrusion, horizontal growth pattern, maxillary protrusion and mandibular retrusion.